2001
DOI: 10.1067/mcp.2001.118366
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the placebo analgesic effect in acute pain

Abstract: The results demonstrated no gender difference in response to placebo. These results were obtained from the post-third molar extraction situation, in which the least possible confounding factors were present. To fully establish the generality of this phenomenon, studies should be carried out in other pain models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 23 publications
(34 reference statements)
2
28
2
1
Order By: Relevance
“…Increasing evidence indicates that women may be more responsive than men to sensory smoking cues, which suggests that they might show greater placebo effects of smoking (e.g., Perkins, Donny & Caggiula, 1999;Perkins et al, 2001) and perhaps NRT. By contrast, clinical research has shown no sex differences in analgesic placebo effects (Averbuch & Katzper, 2001), and greater effects in men than women have been seen in placebo effects of antidepressant medications (Wilcox et al, 1992). Regarding personality factors, the common notion that certain individuals have personalities that make them generally more susceptible to placebo responding has not been supported in the placebo literature (e.g., Bootzin & Caspi, 2002).…”
Section: Individual Differences In Placebo Nicotine Responsesmentioning
confidence: 92%
“…Increasing evidence indicates that women may be more responsive than men to sensory smoking cues, which suggests that they might show greater placebo effects of smoking (e.g., Perkins, Donny & Caggiula, 1999;Perkins et al, 2001) and perhaps NRT. By contrast, clinical research has shown no sex differences in analgesic placebo effects (Averbuch & Katzper, 2001), and greater effects in men than women have been seen in placebo effects of antidepressant medications (Wilcox et al, 1992). Regarding personality factors, the common notion that certain individuals have personalities that make them generally more susceptible to placebo responding has not been supported in the placebo literature (e.g., Bootzin & Caspi, 2002).…”
Section: Individual Differences In Placebo Nicotine Responsesmentioning
confidence: 92%
“…There are, however, a few findings of stronger placebo analgesic responses in males (Berkley et al 2006;Fillingim et al 2009). Others failed to find SGD in placebo response in the post-third molar extraction (Averbuch and Katzper 2001), in transcutaneous electrical stimulation setting (Robinson et al 1998), and pressure algometer test (Olofsen et al 2005). A systemic review of literature shows that placebo response is not sex related in fibromyalgia and painful peripheral diabetic neuropathy (Hauser et al 2011).…”
Section: Sgd In Placebo Analgesiamentioning
confidence: 96%
“…Requiring a 50% symptom improvement to qualify as a treatment responder resulted in 26% placebo responders in diabetic neuropathic pain (Arakawa et al, 2015) but this was lower in other pain conditions (e.g., dental pain: 16%; Averbuch and Katzper, 2001). Similar response rates were reported in migraine (29%; Macedo et al, 2006), fibromyalgia (45%; Hauser et al, 2011), and pancreatic pain (20%; Capurso et al, 2012) investigations.…”
Section: A Effect Sizes Of Symptom Improvement Across Different Medimentioning
confidence: 99%